Technology-Based Adaptive Learning: A Case Study of Ltspice Implementation In The Basic Practice And Electrical Measurement Course - Hamris, Hamidah; Amri, Ariani (Jurnal Pendidikan dan Profesi Keguruan, 2025)
This study employed a case study approach with a descriptive qualitative design to investigate the implementation of technology-based adaptive learning using LTSpice in the Basic Practice and Electrical Measurement course. The research involved 30 students from an experimental group and 30 students from a control group, with an intervention duration of eight weeks. Data were collected through problem-solving ability tests (pretest-posttest), participatory observations, semi-structured interviews, and questionnaires. Quantitative data were analyzed using independent t-tests and N-Gain analysis, while qualitative data underwent thematic analysis. Results showed a significant positive effect of adaptive learning with LTSpice on students' problem-solving capabilities. The experimental group's posttest scores (average 85.20) were significantly higher than the control group's (average 72.80). N-Gain analysis further indicated a high improvement category (average 0.71) for the experimental group, versus a medium category (average 0.30) for the control group. Qualitative findings highlighted improved student engagement, visualization of abstract concepts, independent learning, and positive perceptions from both lecturers and students. It is concluded that LTSpice serves as an effective complementary alternative for hands-on practice, integrating theory and practice for more adaptive and student-centered learning. This study provides strong empirical evidence that LTSpice-based adaptive learning enhances problem-solving capabilities in electrical engineering students, necessitating the development of quality simulation materials and interactive learning activities by lecturers.